1989
DOI: 10.1088/0953-8984/1/48/011
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of hydrogen atoms in the hydrogen bonds of carboxylic acid dimers

Abstract: The techniques of pulsed NMR spectroscopy and inelastic neutron scattering (INS) have been employed to study the coordinated motion of hydrogen atoms in the hydrogen bonds of carboxylic acid dimers. The proton spin-lattice relaxation time T1 has been measured at two frequencies in diglycolic acid and suberic acid and the reorientation rate in diglycolic acid has been measured directly by quasi-elastic neutron scattering. Furthermore T1 data have been collected on benzoic acid, terephthalic acid and malonic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 20 publications
(13 reference statements)
3
39
1
Order By: Relevance
“…(4) and (5) are as follows: E a =30.9 kJ mol À1 , t 0 =1 Â 10 À14 s and C=1.6 Â 10 9 s À2 . It should be noted that these parameters are in an excellent agreement with those obtained for the bromine analogue [27]. According to them we have modified equation.…”
Section: Article In Presssupporting
confidence: 73%
“…(4) and (5) are as follows: E a =30.9 kJ mol À1 , t 0 =1 Â 10 À14 s and C=1.6 Â 10 9 s À2 . It should be noted that these parameters are in an excellent agreement with those obtained for the bromine analogue [27]. According to them we have modified equation.…”
Section: Article In Presssupporting
confidence: 73%
“…This promoted significant progress in the interpretation of T 1 data, particularly that recorded on conventional NMR spectrometers using fixed magnetic field. Horsewill and Aibout [33] studied diglycolic acid, suberic acid, benzoic acid, terephthalic acid and malonic acid achieving a good fit with experimental T 1 data. In similar 1 H T 1 studies, incoherent tunnelling has been observed in 2,5-dinitrobenzoic acid [34] and dodecanoic acid [35].…”
Section: Nmr Relaxometrymentioning
confidence: 75%
“…Some of the early papers [10,13,33] were conducted on less well-characterised samples and display small differences in T 1 compared with more recent studies [41,42,[44][45][46] that have been conducted on very pure, repeatedly zone-refined material.…”
Section: Systematic Uncertainties Associated With Sample Preparationmentioning
confidence: 99%
“…The molecular moiety thought responsible for this motion is therefore the dimeric structure (COOH) 2 , which is known to be present from X-ray diffraction studies. [14] It is well known that in cyclic dimers of many carboxylic acids the two hydrogenbonded protons may undergo fast simultaneous jumps along the hydrogen bonds [17] and a slower p-flip of the whole dimeric structure about its long axis. [18] The parameters obtained from the analysis for the a motion (see Table 3) are compatible with the p-flip of the dimeric structure, based on data previously reported in the literature.…”
Section: Fast Motion Regimementioning
confidence: 99%
“…[18] The parameters obtained from the analysis for the a motion (see Table 3) are compatible with the p-flip of the dimeric structure, based on data previously reported in the literature. [17,18] …”
Section: Fast Motion Regimementioning
confidence: 99%